Density field analysis of a supersonic turbulent boundary layer subject to convex-concave curvature coupling - Ding, Hao; Tian, Lifeng; Huang, Kaiyou; Fu, Shuangxu; Wang, Ao; Xiao, Senhong; Hu, Zhixiong (Physics of fluids (1994), 2025)
This paper presents an experimental investigation on the density field of a supersonic turbulent boundary layers over convex-concave coupled curvatures, utilizing nanoparticle-based planar laser scattering and high-resolution density field measurement techniques. The experiments were conducted in a Mach 3.0 supersonic wind tunnel, employing a opposing curvature model to simulate a typical convex-concave coupled configurations. Transient flow structures were captured, and a quantitative relationship between density and image grayscale was established through oblique shock wave calibration. The results indicate that the combined effect of centrifugal force and favorable pressure gradients in the convex wall suppresses turbulence fluctuations, inducing near-wall relaminarization and significantly reducing the root mean square of density fluctuations. In contrast, the concave wall, due to adverse pressure gradients, triggers multi-scale vortex structures, enhancing outer-layer turbulence disturbances. Multi-resolution analysis of the density field from a time-frequency perspective reveals near-wall turbulence relaminarization and re-transition phenomena, characterized by the quasi-periodicity of large-scale vortices near the wall and the stochastic nature of outer-layer turbulence. The power spectral density distribution of density fluctuations shows that high-frequency turbulent energy in the outer layer of the convex wall is significantly higher than that in the near-wall region, whereas compression effects in the concave wall promote energy concentration at lower frequencies. The analysis of the density field in this study deepens the understanding of the physical nature of turbulent boundary layers over coupled curved walls and provides significant engineering value for the thermal protection material layout of supersonic vehicles.